Functional food consumption in Germany: A lifestyle segmentation study - Annabell Franz; Beate Nowak (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2010)
Due to increasing health consciousness among consumers, there is an ever-growing demand for food and beverages with health-improving components. Not only 'light' and low fat products are in demand, but increasingly so-called well-being products and food which can prevent certain diseases. The German market for functional food is still growing. But who are the German functional food consumers? In an online-survey referring to the Food-Related Lifestyle by BRUNSØ and GRUNERT (1995) we tried to identify different groups of functional food buyers in Germany and to answer the following questions: If there are different consumer groups, how do they vary in their functional food consumption, their buying motives for functional food and their lifestyles? In conclusion, we have identified two different groups of functional food consumers in Germany: The "Health oriented functional food buyers" and the "Convenient functional food buyers" and give recommendations for marketing strategies.
Keywords: 330; functional food; cluster analysis; Food-Related Lifestyle; Gesundheitskost; Nahrungsmittelkonsum; Konsumentenverhalten; Lifestyle; Deutschland